High‐resolution bathymetric mapping reveals subaqueous glacial landforms in the Arctic alpine lake Tarfala, Sweden. (24th July 2019) - Kirchner, Nina; Noormets, Riko; Kuttenkeuler, Jakob; Erstorp, Elias Strandell; Holmlund, Erik Schytt; Rosqvist, Gunhild; Holmlund, Per; Wennbom, Marika; Karlin, Torbjörn
ABSTRACT: In Arctic alpine regions, glacio‐lacustrine environments respond sensitively to variations in climate conditions, impacting, for example, glacier extent and rendering former ice‐contact lakes into ice distal lakes and vice versa. Lakefloors may hold morphological records of past glacier extent, but remoteness and long periods of ice cover on such lakes make acquisition of high‐resolution bathymetric datasets challenging. Lake Tarfala and Kebnepakte Glacier, located in the Kebnekaise mountains, northern Sweden, comprise a small, dynamic glacio‐lacustrine system holding a climate archive that is not well studied. Using an autonomous surface vessel, a high‐resolution bathymetric dataset for Lake Tarfala was acquired in 2016, from which previously undiscovered end moraines and a potential grounding line feature were identified. For Kebnepakte Glacier, structure‐from‐motion photogrammetry was used to reconstruct its shape from photographs taken in 1910 and 1945. Combining these methods connects the glacial landform record identified at the lakefloor with the centennial‐scale dynamic behaviour of Kebnepakte Glacier. During its maximum 20 th century extent, attained c . 1910, Kebnepakte Glacier reached far into Lake Tarfala, but had retreated onto land by 1945, at an average of 7.9 m year –1 . Copyright © 2019 John Wiley & Sons, Ltd.